Utilization of high entropy alloy characteristics in Er-Gd-Y-Al-Co high entropy bulk metallic glass. (15th August 2018) - Kim, Jinyeon; Oh, Hyun Seok; Kim, Jinwoo; Ryu, Chae Woo; Lee, Geun Woo; Chang, Hye Jung; Park, Eun Soo
Abstract: In the present study, we carefully evaluate the role of high entropy alloy (HEA) characteristics on glass-forming ability (GFA) and mechanical responses in a newly developed Er-Gd-Y-Al-Co high entropy bulk metallic glass (HE-BMG) by comparison with the Er-Al-Co and Er-Y-Al-Co bulk metallic glasses (BMGs). The addition of multiple rare-earth elements (REs) to Er-Al-Co BMG results in both higher fragility according to Adam-Gibbs theory and slower crystallization kinetics according to confusion principle. Based on these mutual competitions, the Er18 Gd18 Y20 Al24 Co20 HE-BMG can be successfully fabricated up to 5 mm in diameter for glass formation. In particular, the HE-BMG exhibits unexpected structural bias and more fragile manner via preferential covalent bonding of Co-Al and various RE-Al clusters, which leads to larger deviation from the typical BMGs' behavior in the relation between fragility and elastic properties. Furthermore, the HE-BMG effectively retards crystallization kinetics, which was confirmed by exceptionally sluggish nanocrystallization of multi-precipitates from metastable liquid and longer post-recalescence plateau duration in cooling curve of solidification from stable liquid. Indeed, the increased structural instability due to HEA characteristics (preferential short-range order and sluggish crystallization) in HE-BMGs reduces cut-off size of self-organized shear avalanches and increases the number of chaotic shear avalanches, which can distribute the applied strain more homogeneously, resulting in enhanced intrinsic ductility. Consequently, these results provide a guideline on how to design HE-BMGs with promising properties by utilizing HEA characteristics, and thus can give us a strategy for bridging BMG and HEA. Graphical abstract: Image 1